Safety and feasibility of intravenous administration of a single dose of allogenic-Muse cells to treat human cervical traumatic spinal cord injury: a clinical trial - Masao Koda; Shiro Imagama; Hiroaki Nakashima; Sadayuki Ito; Naoki Segi; Jun Ouchida; Kota Suda; Satoko Harmon Matsumoto; Miki Komatsu; Toshiki Endo; Shinsuke Suzuki; Satoshi Inami; et al. (Stem Cell Research & Therapy)
Abstract Introduction Spinal cord injury (SCI) is a devastating injury and remains one of the largest medical and social burdens because of its intractable nature. According to the recent advances in stem cell biology, the possibility of spinal cord regeneration and functional restoration has been suggested by introducing appropriate stem cells. Multilineage-differentiating stress enduring (Muse) cells are a type of nontumorigenic endogenous reparative stem cell. The positive results of Muse cell transplantation for SCI was shown previously. As a first step for clinical application in human SCI, we conducted a clinical trial aiming to confirm the safety and feasibility of intravenously injected donor-Muse cells. Methods The study design of the current trial was a prospective, multicenter, nonrandomized, nonblinded, single-arm study. The clinical trial registration number was JRCT1080224764. Patients with a cervical SCI with a neurological level of injury C4 to C7 with the severity of modified Frankel classification B1 and B2 were included. A primary endpoint was set for safety and feasibility. Our protocol was approved by the PMDA, and the trial was funded by the Life Science Institute, Tokyo, Japan. The present clinical trial recruited 10 participants (8 males and 2 females) with an average age of 49.3 ± 21.2 years old. All 10 participants received a single dose of allogenic CL2020 (a total of 15 × 106 cells, 2.1–2.7 × 105 cells/kg of body weight), which is a Muse cell-based product produced from human mesenchymal stem cells, by an intravenous drip. Results There were two reported severe adverse events, both of which were determined to have no causal relationship with Muse cell treatment. The change in the ISNCSCI motor score, the activity of daily living and quality of life scores showed statistically significant improvements compared to those data at the time of CL2020 administration. Conclusion In the present trial, no safety concerns were identified, and Muse cell product transplantation demonstrated good tolerability. Future clinical trials with appropriate study designs incorporating a control arm will clarify the definitive efficacy of single-dose allogenic Muse cell treatment with intravenous administration to treat SCI. Trial registration: jRCT, JRCT1080224764. Registered 03 July 2019, https://jrct.niph.go.jp/latest-detail/jRCT1080224764 .